Evidence That Different Cation Chloride Cotransporters in Retinal Neurons Allow Opposite Responses to GABA - Vardi, Noga (J Neurosci, 2000)
GABA gating an anion channel primarily permeable to chloride can hyperpolarize or depolarize, depending on whether the chloride equilibrium potential (E(Cl)) is negative or positive, respectively, to the resting membrane potential (E(rest)). If the transmembrane Cl(−) gradient is set by active transport, those neurons or neuronal regions that exhibit opposite responses to GABA should express different chloride transporters. To test this, we immunostained retina for the K-Cl cotransporter (KCC2) that normally extrudes chloride and for the Na-K-Cl cotransporter (NKCC) that normally accumulates chloride. KCC2 was expressed wherever E(Cl) is either known or predicted to be negative to E(rest) (ganglion cells, bipolar axons, and OFF bipolar dendrites), whereas NKCC was expressed wherever E(Cl) is either known or predicted to be positive to E(rest)(horizontal cells and ON bipolar dendrites). Thus, in the retina, the opposite effects of GABA on different cell types and on different cellular regions are probably primarily determined by the differential targeting of these two chloride transporters.